Myocardial strain by 3D-speckle tracking echocardiography predicts long-term risk of cardiovascular morbidity and mortality in the general population: the Southall And Brent Revisited (SABRE) study. (14th October 2021) - Al Saikhan, L; Park, C; Tillin, T; Williams, S; Jones, S; Manisty, C; Mayet, J; Chaturvedi, N; Hughes, A; ,
Abstract: Background: Both left ventricular (LV) ejection fraction (EF) and Global Longitudinal Strain (GLS) by 2D-echocardiography predict mortality and cardiac events, and GLS may be superior to EF. 3D-speckle tracking echocardiography (3D-STE), a recently validated method, allows simultaneous assessment of EF, GLS and principal tangential strain (PTS), but its prognostic utility in the general population is unknown. Purpose: We hypothesized that 3D-STE derived LV myocardial strains predict a composite of cardiac endpoints, and that GLS would be a better prognostic marker than EF. We also investigated the utility of PTS compared with GLS and EF. Methods: A total of 529 individuals (69±6y; 76.6% male) from SABRE study, a UK-based tri-ethnic community cohort, underwent health examinations. The association between 3D-STE EF or multidirectional myocardial strains and a composite cardiac endpoints comprising coronary heart disease (fatal/non-fatal), heart failure hospitalization, new-onset arrhythmia was determined using Cox proportional hazards models with and without adjustment for potential confounders and Harrell's C statistics were calculated. Associations with cardiovascular (CV) mortality was examined as a secondary objective. The incremental value of 3D-STE EF, GLS and PTS in improving CV risk stratification by the established Framingham risk score (FRS) was investigated using a likelihood ratio test on a series of nested Cox proportional hazards models. Results: During follow-up (median, 8y), there were 56 composite cardiac endpoints and 24 CV deaths. EF and radial strain were negatively associated, while GLS, global circumferential strain and PTS were positively associated with the composite cardiac endpoints in unadjusted models (Table 1). Associations were only marginally affected by adjustment for potential confounders although confidence intervals of the estimate increased slightly (Table 1). There was little difference in the C-statistics for EF, GLS or PTS for the composite cardiac endpoints (Table 1). Associations with CV mortality were generally weaker and only GLS showed some evidence of a positive association with CV mortality in unadjusted and adjusted models (Table 1). Compared to EF and GLS, PTS most improved the predictive value (model fit) of FRS for composite cardiac endpoints (Table 2). None of the measures convincingly improved calibration for CV mortality. Conclusions: 3D-STE-derived LV myocardial strains predicted adverse cardiac events and CV mortality in a multi-ethnic sample of the UK general population. PTS/3D-strain was an independent predictor of cardiac events with some evidence of it being a slightly better predictor than conventional indices of LV function (GLS and EF). Future prospective studies are needed to confirm and extend these findings. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): The main SABRE study is supported by the Wellcome Trust and BHF.